2020
DOI: 10.3389/fonc.2020.01636
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of First-Line Chemotherapy in Patients With Non-small Cell Lung Cancer and Interstitial Lung Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Lung cancer is a well-known comorbidity of interstitial lung disease (ILD), and the actual efficacy and safety of chemotherapy for patients with non-small cell lung cancer and interstitial lung disease (NSCLC-ILD) have not been determined. We conducted this meta-analysis to assess the efficacy and safety of chemotherapy for patients with NSCLC-ILD. Methods: We searched related studies from the Cochrane Library, PubMed, and Embase. The endpoints were objective response rate (ORR), disease control ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In a recent meta-analysis, the AE-ILD rate was 8.07%, and in a subgroup analysis of patients treated with carboplatin and nab-paclitaxel, the AE-ILD rate was 4.98%. 22 On including the case that did not meet our criteria for AE-ILD, the rate of AEs was 12%, which was slightly higher than that reported previously. This rate may have been influenced by the small sample size.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In a recent meta-analysis, the AE-ILD rate was 8.07%, and in a subgroup analysis of patients treated with carboplatin and nab-paclitaxel, the AE-ILD rate was 4.98%. 22 On including the case that did not meet our criteria for AE-ILD, the rate of AEs was 12%, which was slightly higher than that reported previously. This rate may have been influenced by the small sample size.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the AE‐ILD rate among patients in our study was 4%, similar to that found in two prospective studies. In a recent meta‐analysis, the AE‐ILD rate was 8.07%, and in a subgroup analysis of patients treated with carboplatin and nab‐paclitaxel, the AE‐ILD rate was 4.98% 22 . On including the case that did not meet our criteria for AE‐ILD, the rate of AEs was 12%, which was slightly higher than that reported previously.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, patients with diffuse serosal metastases (pericardial, pleural, meningeal, and mesenteric) were excluded from the present study due to their ineligibility for LAT in accordance with the multidisciplinary consensus statement on the definition of oligometastatic NSCLC 21 . In addition, patients with interstitial lung disease were excluded from this study because they tended to have a poor prognosis due to the limited availability of chemotherapy regimens 24,25 …”
Section: Methodsmentioning
confidence: 99%
“…21 In addition, patients with interstitial lung disease were excluded from this study because they tended to have a poor prognosis due to the limited availability of chemotherapy regimens. 24,25…”
Section: Patientsmentioning
confidence: 99%
“…In contrast, chemotherapy may be a more appropriate treatment option. However, our previous meta-analysis indicated that first-line chemotherapy may be associated with a higher rate of acute exacerbation of interstitial lung disease (AE-ILD), the pooled AE-ILD rate was 8.07% (95% CI: 6.12-10.26%) ( 4 ). Therefore, there is an urgent need for new strategies to treat such patients.…”
Section: Introductionmentioning
confidence: 99%